Strategi Membangun Branding Produk Pada Pelaku Usaha Mikro Kecil Menengah di Era Digital di Desa Kesugihan Pulung Ponorogo - Choiru Nisa; Diyan Putri Ayu (Social Science Academic, 2025)
Scientific writing Strategy for building Product Branding for MSME actors in the Digital era. From the studies that have been conducted it shows that MSMEs have an important role in the Indonesian economy, especially in the village area of Kesgihan Pulung Ponorogo. the research method used is descriptive qualitative research. The subjects of this study were several MSME actors, after which the interview data were collected using observation techniques, then analyzed qualitatively. Based on the results of these observations, it was revealed that the aim of the research was to provide assistance in the MSME Product Branding and Digital Branding programs, the focus was on creating logo designs and online marketing on social media and e-commerce platforms for MSME practitioners of traditional herbal medicine. Through a unique logo design and online marketing, it is hoped that these MSME products will become more competitive and durable. Through a unique logo design and online marketing, it is hoped that these MSME products will become more competitive and durable. In addition to local marketing, online marketing measures on Instagram, Gofood and Shopee will develop brand awareness and increase public understanding of products. The data shows that many MSMEs in Kesugihan Village need further understanding of branding and digital marketing. Even though there is a training plan, MSMEs are still hesitant to run an online business because of the hopes of the villagers. This observation effort helps SMEs to adapt to online sales to increase sales and product range. The recommended solution is assistance to understand product branding in digital media, with quality companions to overcome obstacles.